The Dictator Dilemma : The United States and Paraguay in the Cold War - Tyvela, Kirk (Pitt Latin American series., 2019)
The Dictator Dilemmatells the story of US bilateral relations with the Alfredo Stroessner dictatorship (1954-1989). Tyvela focuses on how and why that diplomatic relationship changed during the Cold War from cooperation, based on mutual opposition to communism, to conflict, based on clashing expectations concerning democratic reforms and human rights. The policy debates by officials in Washington and in Asunción brought out a tension that has defined US diplomacy for more than a century: how can the United States partner with tyrants while credibly proclaiming to advance a democratic mission in the world? Tyvela argues that the Stroessner regime was symbolic of a broader foreign policy struggle to perpetuate, enforce, and ultimately redefine the importance of friendly dictators to US global and hemispheric interests.